Analisis Faktor-Faktor yang Berhubungan Dengan Status fungsional pada Pasien Osteoartritis di RSUD Raden Mattaher Jambi Tahun 2018 - Dewi Masyitah (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Osteoarthritis is a degenerative and progressive disease characterized by joint abrasion and formation irregular bone on the surface of the joints. Osteoarthritis causes pain and limits joint mobility. Patients have limitation in functional status that interferes with daily life activities. The purpose of this study was to identify factors related to functional status in patients with osteoarthritis. This research used a cross-sectional design involving 70 patients with osteoarthritis at Raden Mattaher Hospital. Sampel were obtained with purposive sampling and data analysis using chi-square test. The results showed that there was a significant association between pain, age, body mass index and family support with functional status. Joint exercises, pain management and strengthening the role of the family to improve the functional status patients with osteoarthritis.